France : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in France during 1990-95. Partner country demand recovered markedly in the course of 1993, following a sharp downturn since the middle of 1992. The surge of exports during the second half of 1993 was followed by a temporary stabilization at a higher level during the first half of 1994. Strong export growth resumed during the second half of 1994. Overall, French exports of goods and nonfactor services increased by almost 6 percent in 1994. A rapid pace of expansion was maintained during the first half of 1995.